Role and significance of legal customs in national jurisdictions (in terms of the Russian Federation) - Pavlovich Anisimov, Aleksey; Jakovlevich Ryzhenkov, Anatoliy; Viktorovna Sokolskaya, Lyudmila (DIXI, 2021)
In the Russian legal science, there is an established opinion that today legal custom plays a secondary role in the system of sources of law, or even that it is a rudiment and is not required in regulation of social relations anyway. This position of scientists is explained by the fact that theories rejecting custom as a source of law were common in the ussr since the 1920s. There were numerous attempts to substantiate the impossibility and needlessness of its use in a socialist state. It was justified by the fact that custom is a “primitive” form of law that is not capable of efficiently regulating social relations and even hinders their development. Having studied the modern practice of application of customs in various branches of private and public law, the authors give reasons for the conclusion that the scope of legal customs still retains its significance in Russia. It is proved that the role of customs differs in respect of fields of private and public law, occupying an insignificant place within the latter. However, also in that case there is transformation of established ideas about legal customs, their position in the system of sources of law and the role in the system of legal regulation of social relations are revised. The authors of the article substantiate the need to preserve legal custom in the system of sources of law and propose measures to increase the efficiency of their use.
Keywords: forms of law; legal system; legal custom; rules of customary law; sources of law; business custom